Development And Validation Of RP-HPLC Method For The Estimation Of Dapagliflozin In Tablet Dosage Form Using Azelnidipine As An Internal Standard (International Journal of Environmental Sciences, 2025)
A simple, sensitive, precise, and accurate RP-HPLC (Reverse-Phase High-Performance Liquid Chromatography) method was developed and validated for the selective determination of Dapagliflozin using Azelnidipine as an internal standard (IS). An isocratic mode was used through Qualisil-5 BDS-C8(250×4.6mm,5µm) column, packed with 5μm particle utilizing mobile phase composition of Acetonitrile and 0.1% Ortho Phosphoric Acid (OPA), pH adjusted to 3 with Triethylamine (TEA) with a proportion of 50: 50% (v/v). The detection of the analyte was performed at a maximum wavelength of 232 nm and with a flow rate of 1 ml/min of the mobile phase. The run time was 10 mins with retention time of 4 mins for Dapagliflozin. Dapagliflozin was found to be linear in the range of 10-50 µg/ml with correlation coefficient (r2) of 0.9991. The results of the analysis were verified for linearity, accuracy, precision, robustness, limit of detection, and limit of quantification in the developed method. The percentage recovery was found to in the range of 98.40% – 101.11%. Assay of marketed formulation was found to be 99.84%. Method was found to be reproducible with relative standard deviation (%RSD) for intraday and interday precision less than 2. The assessment of robustness of the method indicates that method remains unaffected by slight changes in chromatographic conditions. Thus, the developed RP-HPLC method was found to be simple, specific, rapid, reliable and reproducible.